Ansiedad y su influencia en el desenvolvimiento social en una adolescente de 17 años de edad del Recinto San Joaquín de la ciudad de Montalvo - Vera Calero, María Belén (2021)
Within the present case study regarding anxiety and its influence on social development in a 17-year-old adolescent, which, due to a close experience, such as a motorcycle accident of a relative, has caused fear in her and worry that some other family member and even herself something similar happens. For this case study, techniques and instruments such as semi-structured clinical interviews, clinical observation and psychometric tests such as the Beck anxiety inventory test and the Hamilton test for anxiety were applied, all these techniques and instruments aimed at a cognitive behavioral approach. Since through the clinical examination patterns of anxious behaviors were detected due to their distorted thoughts causing the deterioration of social development in the patient. At the end of the entire process of mental examination, the diagnosis of a generalized anxiety disorder (F41.1) was reached, since it meets the diagnostic criteria of ICD 10 and based on the findings obtained, which were evident, these being: difficulty in thinking, sadness, worry, crying, distorted thoughts, social avoidance, sweaty hands, and rapid heart palpitations. They also proceeded to develop a therapeutic plan focusing on the needs that require change in their mental health.